Investigation of effect of hygrothermal ageing on physical properties of graphene oxide / epoxy nano-composites. (2022) - Manjunatha, G.; Sharma, K.V.
Abstract: The present article investigates the effect of hygrothermal ageing on the physical and mechanical properties of graphene oxide reinforced epoxy/glass composites. Both neat and graphene reinforced composite laminate structures were immersed in hot artificial seawater with different temperatures namely 50 °C and 60 °C for 72 h and then tested for different physical and mechanical properties. Langmuir's model was employed for simulating the physical properties. Fick's law was proposed for the diffusion coefficient and parameters as a function of temperature and graphene content. The results showed that diffusion coefficient, permeability and moisture absorption decrease with the addition of graphene oxide, but glass transition temperature and hardness increase with graphene. The water uptake of graphene oxide reinforced laminates has significantly decreased due to graphene oxide acting as a water barrier in laminates. The improvement in microhardness of graphene oxide reinforced laminates due to strengthened interface bonding and enhanced epoxy stability.